Нормативно-правове та документаційне регулювання ярмаркової торгівлі на Правобережній Україні у другій половині ХІХ – на початку ХХ ст. - Юрченко, Віталіна (Видавництво Львівської політехніки, 2016)
The article deals with normative , legal and document regulations of the fair trade on the Right-Bank Ukraine in the second half of the 19th – early 20th centuries. The public authorities’ documents that regulated trade in cities, towns and villages of the Kyiv, Podil and Volhynia provinces have been revealed. Identified are the types of documents, peculiarities of their composition, record cards formation, and the structures of the main requisites. Determined is the procedure of fairs opening, the dates and places the fairs were held. Displayed are the authorities entitled to perform all these operations.
Keywords: ярмарок; базар; торгівля; ярмаркова площа; Київська; Подільська і Волинська губернії; Губернське Правління; клопотання; постанова; лист-прохання; лист-відповідь; дозвіл; положення; звіт; списки